2014
DOI: 10.1038/tpj.2014.74
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance protein 4 (MRP4) polymorphisms impact the 6-mercaptopurine dose tolerance during maintenance therapy in Japanese childhood acute lymphoblastic leukemia

Abstract: Multidrug resistance protein 4 (MRP4) is involved in the efflux of nucleoside derivatives and has a role in the determination of drug sensitivity. We investigated the relationship between MRP4 genetic polymorphisms and doses of the 6-mercaptopurine (6-MP) and methotrexate. Further, we evaluated the frequency of therapeutic interruption during maintenance therapy in Japanese children with acute lymphoblastic leukemia (ALL). Ninety-four patients received an initial 6-MP dose in the range of 30 − 50 mg m − 2 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 25 publications
3
34
2
Order By: Relevance
“…It was also observed that patients with the AA or AG genotype had higher intracellular 6-thioguanine nucleotides concentration and were at higher risk of leukopenia (Ban et al, 2010). Moreover, it was shown in the Japanese childhood acute lymphoblastic leukemia (ALL) population that the homozygous variant allele in any of the ABCC4 2269G.A, 912C.A, and 559G.T variants was in correlation with reduced 6-MP dose (Tanaka et al, 2014). More recently, Gao et al (2015) reported that 559G.T was significantly associated with decreased intraocular pressure in response to latanoprost.…”
Section: Pharmacogenomics Of Mrp4mentioning
confidence: 86%
“…It was also observed that patients with the AA or AG genotype had higher intracellular 6-thioguanine nucleotides concentration and were at higher risk of leukopenia (Ban et al, 2010). Moreover, it was shown in the Japanese childhood acute lymphoblastic leukemia (ALL) population that the homozygous variant allele in any of the ABCC4 2269G.A, 912C.A, and 559G.T variants was in correlation with reduced 6-MP dose (Tanaka et al, 2014). More recently, Gao et al (2015) reported that 559G.T was significantly associated with decreased intraocular pressure in response to latanoprost.…”
Section: Pharmacogenomics Of Mrp4mentioning
confidence: 86%
“…Guidelines from the Clinical Pharmacogenetics Implementation Consortium (CPIC) are currently being updated to include dosing recommendations for patients with NUDT15 variants [74]. Other genes implicated in differential risk of myelosuppression, that appear to be relevant primarily in persons of East Asian ancestry include multi-drug resistance protein 4 (MRP4) and inosine triphosphate pyrophosphatase (ITPA) [62,75].…”
Section: Hematologic Toxicitymentioning
confidence: 99%
“…ABCC4 encodes multiple drug resistance protein 4 (MRP4), which belongs to the ATP-binding cassette (ABC) transporter family and assists in the efflux of a large variety of therapeutic agents, including 6-MP [24]. Of the 11 missense variants that have been investigated, compared to the wild-type MRP4, the Y556C variant has been associated with significantly higher transport of 6-MP, whereas the V776I, and the rs9516519 T>G polymorphisms have been associated with significantly lower transport 6-MP [25].…”
Section: Pharmacogenetic Considerations For 6-mpmentioning
confidence: 99%